Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/ije/dyaa233
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of intermittent preventive treatment of malaria in pregnancy in four sub-Saharan countries: findings from household surveys

Abstract: Background Intermittent preventive treatment in pregnancy (IPTp) with sulphadoxine-pyrimethamine (SP) is a key malaria prevention strategy in areas with moderate to high transmission. As part of the TIPTOP (Transforming IPT for Optimal Pregnancy) project, baseline information about IPTp coverage was collected in eight districts from four sub-Saharan countries: Democratic Republic of Congo (DRC), Madagascar, Mozambique and Nigeria. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
1
25
2
Order By: Relevance
“…This is of high importance in sub-Saharan Africa, where health systems face both human resource and nancial constraints. However, the low uptake of IPTp3 reported in this study, which is similar to that reported in some sub-Saharan African subregions, (20,27,28) indicates that more improvements in coverage must be made in order to reach the Sustainable Development Goal Target 3.3, to end the malaria epidemic (in addition to the AIDS and tuberculosis epidemics). Future research should explore barriers and facilitators of CHWs interventions to best inform scale-up of these programs.…”
Section: Conclusion and Recommendationssupporting
confidence: 79%
“…This is of high importance in sub-Saharan Africa, where health systems face both human resource and nancial constraints. However, the low uptake of IPTp3 reported in this study, which is similar to that reported in some sub-Saharan African subregions, (20,27,28) indicates that more improvements in coverage must be made in order to reach the Sustainable Development Goal Target 3.3, to end the malaria epidemic (in addition to the AIDS and tuberculosis epidemics). Future research should explore barriers and facilitators of CHWs interventions to best inform scale-up of these programs.…”
Section: Conclusion and Recommendationssupporting
confidence: 79%
“…and how many times did you receive SP/Fansidar during this pregnancy?” For statistical analysis, the uptake of at least one dose of IPTp-SP was categorised and coded into 0 = no dose of IPTp-SP and 1 = at least one dose of IPTp-SP (≥1 dose). The uptake of optimal doses of IPTp-SP was categorised and coded into 0 = two or fewer doses (≤ 2 doses) and 1 = at least three doses of IPTp-SP (≥ 3 doses) (10, 21)…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that pregnant women’s attitudes and motivation to receive IPTp-SP was related to their levels of knowledge of malaria-related factors such as morbidities caused by malaria (8, 9). Similarly, region, religion, age, and marital status influenced the number IPTp-SP doses received during pregnancy (8,10,11). Socioeconomic considerations including education level, spouse’s education level, employment status, health insurance coverage and household wealth index influenced IPTp-SP uptake (12, 13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO recommends a minimum of three doses of IPTp (IPTp3+) with universal coverage of at least 80% of pregnant women [ 1 ]. However, in DRC, IPTp3+ implementation is less than the universal coverage and the majority of women attending at least four antenatal care visits receive less than three doses of IPTp [ 1 , 98 ]. Despite the increase in SP falciparum resistance in DRC [ 99 , 100 , 101 , 102 , 103 , 104 ], IPTp is still used for malaria prevention during pregnancy and protection against maternal anemia and low birthweight; especially when it is given in three or more doses [ 101 ], as shown in other countries [ 105 , 106 , 107 , 108 , 109 ].…”
Section: Current Drc Malaria Control Policymentioning
confidence: 99%